Viajes azarosos: la aventura de la insularidad en la narrativa puertorriqueña: Vecindarios excéntricos de Rosario Ferré - Rodríguez, Fátima; Tudoras, Laura Eugenia (Revista de Filología Románica, 2005)
This work focuses on the being from Puerto Rico such as identity. This subject is recovered by the narrative speech of Vecindarios Excéntricos by means of a double symbol: the island and the travel.
Keywords: Narrative; Puerto Rico; Island; Travel